A Systematic Literature Review on Technical Debt in Software Development: Types, Tools, and Concerns - Terrón-Macias, Victor; Mejia, Jezreel; Terrón-Hernández, Miguel (International Journal of Combinatorial Optimization Problems and Informatics, 2025)
Software projects often accumulate technical debt, which undermines code quality, maintainability, and long-term viability. This article analyses twelve categories of technical debt and examines the capabilities of existing mitigation tools. To achieve this, we conducted a systematic literature review. Based on the results, we categorise and describe each debt type as it occurs in practice, and we assess prominent tools (such as AnaConDebt, CAST, DebtFlag, Visminer TD, and TD-Tracker) with respect to the debt types they target, the programming languages they support, and their adherence to established software quality models or methodologies. Our analysis shows that most current solutions focus on code and architectural debt, whereas documentation and process debt remain largely unaddressed. Moreover, most tools do not conform to software quality models or standards, which none of them explicitly incorporate. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2025.v16i4.1150